Morphometric parameters of the umbilical cord within the standart at infringenment of the formation of the placenta. - Abdul-Ogly, L. V.; Kozlovskaja, A. A.; Rutgayzer, V. G.; Dubovik К. I.; Belskaya Е. О. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Infringements of the formation of the umbilical cord, first of all, are connected with the vessels, being located in it, which depending on the high-grade development have the various period of the torsion and, hence, the period of the reciprocal pulsation, providing the trophic function for a placenta and, further for an embryo and a fetus. As a result, the important indicator of the development of the umbilical cord is its anthopometrical data. Objective To study morphometric parameters of the umbilical cord within the standart at infringenment of the formation of the placenta. Methods. A study exstraembryonic organ was conducted on embryos 8 - 42 weeks. Research was conducted on embryos of man of prenatal ontogenesis. Results. As a result of researches we have defined laws of changes of morphometric parameters of the umbilical cord at the infringement of the differentiation of the chorionic villi as result of the infringement of epithelial-mesenchymal transformations. As a result of researches at the development of the chorion in norm by the 9th week of the development the quantity of coils equels 11, and by the termination of the first trimester (by the 13th week) - 14 curls. Thus, within 4 weeks, the formation of 5 curls was on the average observed. It is necessary to notice, that in embryogenesis the intensity of the formation of curls is more expressed in comparison with the fetal period considering morphometric parameters. Conclusion So, the length of the umbilical cord had been changed during the fetal period of the prenatal ontogenesis with 17,0 ± 1,3 sm in 13 - 15 weeks up to 62,7 ±0,5 in 40 - 42 weeks, and the quantity of curls had varied from 8 -9 in 9 weeks up to11 in 13 weeks.